PERAN GURU PENGGERAK DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMA NEGERI 1 TIBAWA PROVINSI GORONTALO - Herinda Mardin; Ilyas H. Husain; Hartono D. Mamu (Jurnal Bionatural, 2024)
An independent curriculum that emphasizes the learning process to meet the learning needs and characteristics of students. Driving teachers are the spearhead in implementing the independent curriculum, their role is very important. The aim of this research is to explain the role of driving teachers in implementing the independent curriculum at SMAN 1 Tibawa in Gorontalo Province because their role is important and difficult. This research is qualitative research using descriptive analysis techniques with library research. This research aims to determine the role of the 9 driving teachers at SMAN 1 Tibawa in the implementation of the Merdeka curriculum. The data collection technique used a questionnaire on the role of teachers in implementing the Merdeka curriculum and analyzed using descriptive analysis techniques. The results of this research are that the role of the driving teacher in implementing the Merdeka curriculum at SMA Negeri 1 Tibawa, Gorontalo Province consists of 6, namely First, a driving teacher functions as a driving force in the learning community for his fellow teachers at school and in his environment. In this situation, teachers act as coaches for other teachers to improve their own abilities; secondly, they act as a driving force to improve student leadership in a better way; third, they are responsible for creating a forum or platform for discussion and collaboration with other teachers and working together to improve the quality of learning; fourth, they are responsible for creating a pleasant, calm and comfortable learning atmosphere for all students; Fifth, driving teachers must always develop themselves which of course has an impact on improving the quality of learning; sixth, driving teachers as motivators for students and other teachers.